1999
DOI: 10.1021/jm990287e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Studies on G-Quadruplex Complexes of Telomerase Inhibitors:  Structure−Activity Relationships

Abstract: Inhibition of the ability of the enzyme telomerase to add telomeric repeats to the end of chromosomes is a novel target for potential anticancer therapy. This paper examines the hypothesis that compounds possessing a planar aromatic chromophore inhibit telomerase via stabilization of, and binding to, a folded guanine quadruplex structure. Two series of telomerase inhibitors have been designed based on the 2,6-disubstituted amidoanthracene-9,10-dione and 3,6-disubstituted acridine chromophores in order to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
138
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 23 publications
6
138
0
1
Order By: Relevance
“…One promising class of quadruplex selective ligands are perylene diimides (PDIs) [35][36][37][38][39][40][41][42][43]. Recent solution studies of N,N=-bis [2-(1-piperidino)-ethyl]-3,4,9,10-perylenetetracarboxylic acid diimide (PIPER) [35] and N, N=-bis(4-morpholinylpropyl)-3,4,9,10-perylenetetracarboxylic acid diimide (Tel01) [38] indicate that these molecules exhibit G-quadruplex affinity by stacking on the faces of the terminal G-tetrads, thereby stabilizing the G-quadruplex structure.…”
mentioning
confidence: 99%
“…One promising class of quadruplex selective ligands are perylene diimides (PDIs) [35][36][37][38][39][40][41][42][43]. Recent solution studies of N,N=-bis [2-(1-piperidino)-ethyl]-3,4,9,10-perylenetetracarboxylic acid diimide (PIPER) [35] and N, N=-bis(4-morpholinylpropyl)-3,4,9,10-perylenetetracarboxylic acid diimide (Tel01) [38] indicate that these molecules exhibit G-quadruplex affinity by stacking on the faces of the terminal G-tetrads, thereby stabilizing the G-quadruplex structure.…”
mentioning
confidence: 99%
“…The protonated heterocyclic nitrogen atom (Compound 5) at physiological pH interacts G-quadruplex by increasing electron deficiency (IC 50 1.35 µM) [13]. In the acridine chromophore aniline substituent at 9 th position shows significant inhibitor activity for the Compound 6 (BRACO19) (IC 50 0.095 µM) and Compound 7 (IC 50 0.060 µM) [14].…”
Section: Acridine Derivativesmentioning
confidence: 99%
“…Wheelhouse et al [24] reported cationic porphyrins, and among them, they found one of the Compound 23 (TMPyP4- [5,[10][11][12][13][14][15]20-tetra-(-N-Methyl-4-pyridyl)] porphine) as it stabilizes and stacked with G-Quadruplex DNA and inhibits telomerase enzyme with an IC 50 value of 6.5±1.4 µM. Analogs of TMPyP4 (e.g., Compound 24 -IC 50 5 µM) have been reported and found as the positively charged substituent's on meso positions, and the size of substitution are important, and the face of porphyrins should be available for stacking [25].…”
Section: Porphyrine Derivativesmentioning
confidence: 99%
“…This makes telomerase in PNET, as in other cancers, a potentially useful diagnostic marker as well as a therapeutic target (White et al, 2001). Reported telomerase inhibitors include antisense oligodeoxynucleotides (Feng et al, 1995), ribozymes (Folini et al, 2000; Yokoyama et al, 1998), RT inhibitors (Strahl andBlackburn, 1996), G-quadruplex interacting compounds Read et al, 1999), small molecule inhibitors (Naasani et al, 1999), isothiazolone derivatives (Hayakawa et al, 1999), rhodacyanine derivatives (Wadhwa et al, 2002), and natural compounds including EGCG, the major polyphenol in green tea (Fujiki et al, 2001;Kinjo et al, 2002;Lyu et al, 2002;Naasani et al, 1998Naasani et al, , 2003. EGCG has been identified as a telomerase inhibitor with anticarcinogenic effects in various animal organs such as the esophagus, stomach, duodenum, colon, liver, pancreas, lung, breast, and skin (Naasani et al, 1998(Naasani et al, , 2003Suganuma et al, 1999).…”
mentioning
confidence: 99%